Use of BD BACTEC™ MGIT™ for the detection of non-tuberculous mycobacteria in sanitary water samples - Ferraro, Vincenzo; Bisognin, Francesco; Sorella, Federica; Ruin, Federica; Dal Monte, Paola (Frontiers in Microbiology, 2024)
Introduction The most commonly used method for the detection of non-tuberculous mycobacteria (NTM) is culture in BD BACTEC™ MGIT™ Mycobacteria Growth Indicator Tubes incubated in an automated growth detection reader BD BACTEC™ MGIT™ 960 Instrument. The system is currently validated for the detection of mycobacteria from clinical specimens but not environmental matrices. Methods From November 2018 to December 2023, 1,369 sanitary water samples from 92 heater–cooler units (HCUs) and 747 sanitary water samples from 489 haemodialysis instruments (dialysis) were concentrated, decontaminated, and cultured on MGIT and solid Lowenstein–Jensen media to evaluate the presence of NTM. NTM-positive cultures (n = 261 HCUs and n = 20 dialysis) were purified by Middlebrook 7H11 agar plate subcultures and identified by MALDI-TOF mass spectrometry technology. Results The purpose of this study was to evaluate the accuracy and reproducibility of the MGIT system on sanitary water from HCU and dialysis, using the two strains most frequently isolated on these devices as sources of NTM during the Emilia- Romagna surveillance programme: M. chimaera (79%) and M. saskatchewanense (100%), respectively. To evaluate the accuracy, sanitary water was spiked with M. chimaera and M. saskatchewanense at the theoretical concentrations of 100 and 10 CFU/mL, and all resulted positive in MGIT tubes. No significant changes in time to positivity were observed when MGIT tubes were inoculated with NTM at the theoretical concentrations of 10 and 100 CFU/mL on 3 consecutive days, indicating that the detection method is reproducible. Discussion The MGIT system is suitable for detecting the presence of NTM in sanitary water samples as it was capable of detecting up to 4 CFU/mL for both M. chimaera and M. saskatchewanense. Our results indicate that the MGIT system can be used for NTM detection not only for clinical samples but also for environmental matrices.